(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study seeks to explore the status of rural, agricultural women within short story narratives—portrayed as women who derive their existence through their productivity, laborious work, and persistent movement both inside and outside the home. The "textual" descriptive lens focused on the village environment has generated a set of cumulative descriptors concerning women, emphasizing their dominant presence in that setting. Using a descriptive-analytical methodology, the scope of the study will be limited to short stories that depict the agricultural countryside of the Al-Baha region in southern Saudi Arabia. This focus is due to the particularly prominent depiction of women in close association with the rural land—an essential element of the study—as expressed by authors native to this region. Furthermore, the limited scope of the research necessitates confining the study to a specific geographical area, which also shares cultural customs and perspectives with other rural settings globally.